2020
DOI: 10.1002/admt.202000810
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Twistable Resistive Switching Memory with Information Storage and Computing Functionalities

Abstract: High‐performance stretchable and twistable nonvolatile memory devices with logic‐in‐memory functionality are highly desired for the development of future wearable electronics such as smart clothing. However, it is challenging to fabricate these memory devices using rigid functional materials based on conventional film deposition and patterning techniques. Herein, the first intrinsically stretchable and twistable resistive switching memory is reported using spin‐coated poly(dimethyl siloxane) elastomer as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Given intrinsically conductive electrodes underpin the electrochemical performance of devices, the conductivity of these conjugated organic materials must not be compromised under the typically mechanical stresses and strains that are encountered when wear electronics. Indeed, this remains the principal challenge of the field, despite the many fabrication [11] and performances [12,13] improvements of stretchable devices.…”
Section: Introductionmentioning
confidence: 99%
“…Given intrinsically conductive electrodes underpin the electrochemical performance of devices, the conductivity of these conjugated organic materials must not be compromised under the typically mechanical stresses and strains that are encountered when wear electronics. Indeed, this remains the principal challenge of the field, despite the many fabrication [11] and performances [12,13] improvements of stretchable devices.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that a choice of substrates with optimized mechanical properties can further increase the flexibility of GFETs since other components involved, that is, the ion‐gel and graphene, can obviously endure higher mechanical stresses. [ 44 ] The nonvolatile and retention properties were characterized by measuring the drain current after the cyclic test. Even after 1000 cycles of bending, the retention characteristics of the Ti 3 C 2 T X /TiO 2 ‐nanoflake‐incorporated ion‐gel gated GFETs were similar to those in the initial state, as shown in Figure 6b.…”
Section: Resultsmentioning
confidence: 99%
“…(B) The wearable healthcare-monitoring device integrated with Ag 2 S-based stretchable memristive devices (Jo et al, 2021). (C) The implementation of the MIG logic with the memristive device (Lu et al, 2021). (D) The stretchable memristive crossbar array with a resistive switching layer of composite material (TPU: Ag NPs) under stretching strain (Yang et al, 2018).…”
Section: Materials Innovation For Stretchable Memristive Arraysmentioning
confidence: 99%
“…Organic-based stretchable memristive devices such as PDMS/ carbon nanotubes (CNTs)/maltoheptaose-block-polyisoprene (MH-b-PI)/Al (Hung et al, 2017) and Cu@GaIn/PDMS/Cu@ GaIn (Lu et al, 2021) have been extensively studied. For instance, Lu et al successfully demonstrated stretchable and twistable PDMS-based memristive devices for in-memory digital computing (Lu et al, 2021) (Figure 4C). On the basis of FIGURE 5 | Stretchable memristive array with structural design for in-memory computing.…”
Section: Materials Innovation For Stretchable Memristive Arraysmentioning
confidence: 99%